Early Cretaceouys gastropods from west-central Argentina and their palaeoecological and palaeobiogeographic affinities - Cataldo, Cecilia Soledad; Lazo, Dario Gustavo
The Lower Cretaceous outcrops of the Argentinean Neuquén Basin bear an abundant and relatively diverse marine gastropod fauna that was scarcely studied in the past and required a thorough taxonomic revision. Also, its palaeoecological and palaeobiogeographic implications were not assessed so far. The present work is based on the revision of former collections in addition to further field collecting. More than 2200 specimens were studied, coming from 39 localities in west-central Argentina where the Lower Valanginian-Lower Barremian bearing units are exposed. The taxonomic study revealed the presence of 26 gastropod species belonging to 20 genera and 18 families. Eight taxa were recorded for the first time in this basin. This fauna shows palaeobiogeographic affinities at different taxonomic levels with the lower Cretaceous gastropods from the Andean basins of Chile, Peru, northwest South America, the Argentinean Austral Basin, the Antarctic Peninsula, the Tethys area and northern Europe. The palaeoautoecology of the recorded taxa was evaluated and a predominance of epifaunal over semi-infaunal and infaunal species was found. Also, epifaunal grazing and/or deposit feeding were more common, although several carnivore species were present. This work represents a landmark advance in our knowledge of the Lower Cretaceous gastropod faunas of the Southern Hemisphere. Fil: Cataldo, Cecilia Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina Fil: Lazo, Dario Gustavo. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; ...